2020
DOI: 10.1021/acsomega.9b03781
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Tetracycline by Shrimp Shell Waste from Aqueous Solutions: Adsorption Isotherm, Kinetics Modeling, and Mechanism

Abstract: The highly efficient removal of tetracycline (TC) from an aqueous solution was accomplished by using the raw shrimp shell waste (SSW) as an environmentally friendly adsorbent. The SSW without any treatment removed TC more efficiently than the SSW after being treated with HCl and NaOH solutions. The SSW was characterized using nitrogen adsorption–desorption isotherms, scanning electron microscopy alongside energy-dispersive X-ray spectroscopy, Fourier transform infrared spectroscopy, a thermogravimetric-derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…On the IR spectrum of TC-activated carbon, it was noticed the vibration bands at 1137, 1441, 1638 and 3420 cm -1 , were assigned to the stretching vibrations C-O-C (1137 cm -1 ), C-N (1441 cm -1 ), C=O (1638 cm -1 ) and O-H (3420 cm -1 ). The absence of the -OH band is noted on the TC-activated carbon_318K spectrum [187,188]. However, a vibration band at 1551 cm -1 that appears on IR spectrum of GM was assigned to the C=C stretching vibration at rings [188,189].…”
Section: Xrd Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…On the IR spectrum of TC-activated carbon, it was noticed the vibration bands at 1137, 1441, 1638 and 3420 cm -1 , were assigned to the stretching vibrations C-O-C (1137 cm -1 ), C-N (1441 cm -1 ), C=O (1638 cm -1 ) and O-H (3420 cm -1 ). The absence of the -OH band is noted on the TC-activated carbon_318K spectrum [187,188]. However, a vibration band at 1551 cm -1 that appears on IR spectrum of GM was assigned to the C=C stretching vibration at rings [188,189].…”
Section: Xrd Methodsmentioning
confidence: 94%
“…The absence of the -OH band is noted on the TC-activated carbon_318K spectrum [187,188]. However, a vibration band at 1551 cm -1 that appears on IR spectrum of GM was assigned to the C=C stretching vibration at rings [188,189].…”
Section: Xrd Methodsmentioning
confidence: 94%
“…Indeed, other similar studies that used crushed shrimp shell and magnetic biochar as adsorbents found that pH 7 was optimal for tetracycline adsorption since the inhibitory electrostatic repulsion under high and low pH conditions were reduced. This is due to Tetracycline predominantly existing in its neutral state at pH 7, in addition to the adsorbent surface being neither highly protonated or deprotonated under conditions of neutral pH (Chang et al, 2020;Li et al, 2019). It can therefore be suggested that hydrogen bonding and π-π EDA interactions are two key adsorption mechanisms under the applied experimental conditions, where these are less dependent on conditions of pH compared with electrostatic interactions between the biochar and tetracycline.…”
Section: Adsorption Kinetics and Isothermsmentioning
confidence: 99%
“…and TCy (adsorbate). The positive value of b T indicates that the adsorption process of TCy onto IL@mAC was endothermic [50].…”
Section: Modeling Of Tcy Adsorption Onto Il@macmentioning
confidence: 99%